Chronic Posttraumatic Dislocation of Radial Head With Ulnar Nerve Entrapment in a Child: A Case Report and Literature Review. Issue 6 (June 2016) - Cai, Jiangyu; Wang, Wei; Yu, Shiyang; Yan, Hede; Zhan, Yulin; Fan, Cunyi
Abstract : Abstract: We present an unusual case of chronic posttraumatic anteromedial dislocation of radial head with direct ulnar nerve entrapment in a child. Ulnar nerve decompression, open reduction of the radial head, and annular ligament reconstruction using a palmaris longus tendon graft were performed, and a satisfactory functional outcome was achieved at the 15-month follow-up. Through a review of literature, we conclude that early diagnosis and management for radial head dislocation are recommended to avoid nerve symptoms. Besides, open reduction and annular ligament reconstruction with a palmaris longus tendon graft would be an alternative surgery during chronic phase.